不完全链匀速往复摆动机构设计研究 - 茅矛; 王成军; 马履中; 沈元锡; 徐燕云; 刘家臻; 王莹 (Jixie chuandong)
In the operation of clear-out,maintenance and processing in exterior of the oil and chemical industrial flow pipes,the manipulators should be the implement to swing at even speed and move in the straight line when actuating source is rotating in a positive direction. To achieve object,the difficult point lies in the design of uniform and reciprocating oscillation device. It is studied that uniform oscillation of the manipulator is achieved by an incomplete-roller chain devie,When rotation direction of driving souree is not changed. The kinetic principle of the device is stated. By an example,design method of the device is analyzed. The device has been applied in an automatic cleaning and spraying robot,the results show that there is feature of compact structure and high reliability for unifrom and recipocating oscillation device of incomplete-roller chain.